2021
DOI: 10.3390/ma14216233
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Properties of the TiNbTaZrO Orthodontic Wire—A Laboratory Comparison to Popular Archwires

Abstract: Background. This study aimed to determine the kinetic frictional force (FF) of the recently produced TiNbTaZrO (Gummetal) orthodontic wire and compare it to the widely used wires of stainless steel (SS), nickel-titanium (NiTi), cobalt-chromium (CoCr) and titanium-molybdenum (TiMo) alloys. Methods. Five types of 0.016″ × 0.022″ wires were ligated with elastic ligatures to 0.018″ × 0.025″ SS brackets. The dynamic FFs between the brackets and ligated wires were measured utilizing a specialized tensile tester mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…When comparing the frictional properties of different alloys, Gummetal falls in between. It is superior to stainless steel alloy wire and inferior to titanium-molybdenum alloy wire [12]. Considering its low friction, Kopsahilis et al stated that Gummetal is a helpful addition in daily orthodontic practice [13].…”
Section: Resultsmentioning
confidence: 99%
“…When comparing the frictional properties of different alloys, Gummetal falls in between. It is superior to stainless steel alloy wire and inferior to titanium-molybdenum alloy wire [12]. Considering its low friction, Kopsahilis et al stated that Gummetal is a helpful addition in daily orthodontic practice [13].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to many previous studies that have suggested that the lowest frictional resistance is achieved with archwire alloys made of SS. [ 31 40 41 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…All the collected shots with good measurement data are then transformed into a spatial three-dimensional image. Such a microscope also covers the micro and meso scales, so in addition to topography [42] of the surface it is also excellent for measuring geometric features in a wide variety of applications [43]. In this regard, there have also been very significant developments in recent years.…”
Section: Measurement Technologies For Metrology 40mentioning
confidence: 99%